Dynamic Imaging of CD8(+) T cells and dendritic cells during infection with Toxoplasma gondii. - Beena John (Public Library of Science (PLoS), 2009)
To better understand the initiation of CD8(+) T cell responses during infection, the primary response to the intracellular parasite Toxoplasma gondii was characterized using 2-photon microscopy combined with an experimental system that allowed visualization of dendritic cells (DCs) and parasite specific CD8(+) T cells. Infection with T. gondii induced localization of both these populations to the sub-capsular/interfollicular region of the draining lymph node and DCs were required for the expansion of the T cells. Consistent with current models, in the presence of cognate antigen, the average velocity of CD8(+) T cells decreased. Unexpectedly, infection also resulted in modulation of the behavior of non-parasite specific T cells. This TCR-independent process correlated with the re-modeling of the lymph node micro-architecture and changes in expression of CCL21 and CCL3. Infection also resulted in sustained interactions between the DCs and CD8(+) T cells that were visualized only in the presence of cognate antigen and were limited to an early phase in the response. Infected DCs were rare within the lymph node during this time frame; however, DCs presenting the cognate antigen were detected. Together, these data provide novel insights into the earliest interaction between DCs and CD8(+) T cells and suggest that cross presentation by bystander DCs rather than infected DCs is an important route of antigen presentation during toxoplasmosis.